Proces Gdański . Gdańsk Trial - Tymczasowa Komisja Koordynacyjna NSZZ "Solidarność". (Tymczasowa Komisja Koordynacyjna NSZZ "Solidarność", 1985)
Double-side, b&w print on white paper. The front-side of the flier, issued on the occasion of the conviction of Adam Michnik, Bogdan Lis and Władysław Frasyniuk by the Gdańsk court, presents the photos of the convicted and informs about the lenght of their sentences. On the backside, the flier contains a text which criticizes the unjust character of the verdict and acknowledges the support given to the political prisoners both at home and abroad.